Oral Antibiotics and Organ Space Infection after Appendectomy and Intravenous Antibiotics Therapy for Complicated Appendicitis in Children - Morita, Kaori; Fujiogi, Michimasa; Michihata, Nobuaki; Matsui, Hiroki; Fushimi, Kiyohide; Yasunaga, Hideo; Fujishiro, Jun (European Journal of Pediatric Surgery, 2022)
Background There is little consensus regarding management after appendectomy for complicated appendicitis in children. Recent literature suggests that patients may be safely discharged without oral antibiotics after adequate intravenous antibiotics therapy. We conducted a nationwide retrospective cohort study comparing the proportion of postoperative organ space infection between patients discharged with and without oral antibiotics after appendectomy followed by intravenous antibiotics therapy for complicated appendicitis.Methods Using the Diagnosis Procedure Combination database, we identified patients between 3 and 18 years of age who had undergone appendectomy for complicated appendicitis between July 2010 and March 2018. Propensity score–matched analyses were performed to compare outcomes between the groups with and without oral antibiotics. The primary outcome was readmission due to organ space infection within 60 days of discharge and the secondary outcome was 60-day readmission due to any reason. Additionally, we conducted a stabilized inversed probability of treatment weighting analysis as a sensitivity analysis.Results We identified 13,100 eligible patients who had received oral antibiotics (n = 3,501) and who had not received oral antibiotics (n = 9,599). Propensity score matching created 2,769 pairs. Readmissions due to organ space infection were 3.4% and 5.2% in the nonusers and users of oral antibiotics, respectively (p = 0.007). The oral antibiotics users also had a significantly higher proportion of readmission due to any reason than the nonusers (5.5 vs. 7.4%, p = 0.004). The sensitivity analyses demonstrated consistent results.Conclusion Among children who had undergone appendectomy for complicated appendicitis, oral antibiotics following discharge after adequate intravenous antibiotics therapy may increase organ space infection.
Keywords: appendectomy; complicated appendicitis; intravenous antibiotics therapy; organ space infection